2019
DOI: 10.3390/su11072155
|View full text |Cite
|
Sign up to set email alerts
|

Research on Economic Bearing Capacity of Farmers to Agricultural Irrigation Water Prices in the Ebinur Lake Basin

Abstract: The Ebinur Lake Basin is one of the few lakes in the arid area of northwest China where water shortages have always been an important factor hindering development. Therefore, this study takes as its objective an investigation of water prices as the main economic factor that restricts the sustainable utilization of water resources to explore the economic affordability of water prices for farmers. Furthermore, the study attempts to determine the appropriate range of prices for water price reform. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The surface area of Lake Ebinur showed an increasing trend before 2003; thereafter, it showed a rapid decline from 885 km 2 in 2003 to 392 km 2 in 2015 [ 28 ]. This reduction was because from 2003 to 2015, the gross regional product of the two major cities in the ELB region, Bole city, and Jinghe County, increased by 11.210 billion yuan and 5.516 billion yuan, respectively, while the area of sown crops increased by 34,700 hectares and 6.58 hectares, respectively [ 60 , 61 ]. These dramatic economic activities consumed many water resources in the ELB.…”
Section: Discussionmentioning
confidence: 99%
“…The surface area of Lake Ebinur showed an increasing trend before 2003; thereafter, it showed a rapid decline from 885 km 2 in 2003 to 392 km 2 in 2015 [ 28 ]. This reduction was because from 2003 to 2015, the gross regional product of the two major cities in the ELB region, Bole city, and Jinghe County, increased by 11.210 billion yuan and 5.516 billion yuan, respectively, while the area of sown crops increased by 34,700 hectares and 6.58 hectares, respectively [ 60 , 61 ]. These dramatic economic activities consumed many water resources in the ELB.…”
Section: Discussionmentioning
confidence: 99%
“…If prices at least partially reflect production costs, generally WTP should decline with higher prices. Much recent research on demand reduction through pricing, however, often adopts a standard economic approach, notably use of price and income elasticities (e.g., [18,28]). Such understanding is usually necessary, but frequently not sufficient (e.g., [5,29]).…”
Section: Willingness To Pay For Water In the Kuwaiti Contextmentioning
confidence: 99%
“…Some countries take affordability into account when pricing. Latinopoulos [1,2] indicated that the pricing for agricultural irrigation water in the eastern United States is "service cost + user affordability". In the reform of agricultural water prices, France chose the pricing model of "full cost + user affordability" for irrigation water pricing [3].…”
Section: Introductionmentioning
confidence: 99%